The teaching of literature to less proficient students in rural secondary schools in Kelantan / Radzuwan Ab. Rashid - Ab. Rashid, Radzuwan (2012)
This study aims to identify the approaches and strategies employed by teachers in teaching the literature component to less proficient students in selected secondary schools in Kelantan, Malaysia. A total of 120 teachers and 240 students from 20 rural schools participated in this research. The approaches and strategies used by teachers in the literature lessons were identified while the reasons to why the teachers employed the approaches and strategies were explicated. Students' feedback on the approaches and strategies employed were also acknowledged. Data from questionnaires, classroom observations and semi-structured interviews were triangulated to form the findings for this study. Findings showed that the informationbased approach (24%) is the most frequently employed by teachers, followed by moral-philosophical approach (23%) and paraphrastic approach (20%). This seems to reflect the findings of classroom observations whereby all the teachers exhibited the use of similar teaching approaches. The findings indicate that the tendency of using teaching approach is influenced by the students' low level of language proficiency which results in teachers providing answers and facts to them. Apart from that, teachers were frequently observed to be using Bahasa Malaysia as a medium of instruction. The implication is that literature teaching with the aims of developing students' language and thinking skills and generating students' personal response and appreciation may not be successfully achieved.